Синтез суміщеного автомата зі зменшенням площі нано-ПЛМ - Баркалов, О.О.; Тітаренко, Л.О.; Візор, Я.Є.; Матвієнко, О.В. (Control systems & computers, 2020)
Пропонується метод зменшення площі схеми суміщеного автомата, в базисі нано-ПЛМ. Метод заснований на оптимальному кодуванні станів автомата Мура, який враховує наявність класів псевдоеквівалентних станів. При цьому виділяється частина схеми, яка реалізує функції автомата Мура. Запропонований метод дає змогу зменшити площу нано-ПЛМ, необхідну для реалізації схеми, в порівнянні з тривіальною дворівневою схемою. Наведено результати досліджень і приклад синтезу схеми автомата. Purpose. Among the models that are used for the synthesis of control devices, a significant place is occupied by the model of combined microprogram automation (CMPA). However, methods for the synthesis of CMPA schemes in the nano-PLA basis are currently lacking. Due to the importance of this problem, we propose a method for the synthesis of CMPA on nano-PLA basis. Methods. For the specification of CMPA, the language of graph diagrams of the algorithm is used. The method proposed in the article is based on the optimal coding of states of the Moore FSM, taking into account the existence of classes of pseudoequivalent states (PES). In this case, a part of the circuit that implements the functions of the Moore automation is highlighted. Results. The method allows to reduce the nano-PLS area in comparison with the trivial two-level scheme. Studies conducted on the basis of the standard library showed that the proposed method allows on average 35% decrease in the comple-xity of the matrix CMPA scheme. At the same time, a decrease in the length of the direct structural table was achieved for 38% of the examples, and a decrease in the number of matrix entries for 16%. Moreover, the maximum decrease in area reached 67%. For 14% of the examples, the area did not decrease. Цель статьи. Среди моделей, которые используются для синтеза устройств управления, существенное место занимает модель совмещенного микропрограммного автомата (СМПА). Однако методы синтеза схем СМПА в базисе нано-ПЛМ в настоящее время отсутствуют. В силу важности этой проблемы, в настоящей статье предлагается метод синтеза СМПА на нано-ПЛМ.